The Integration of Islamic Religious Education Curriculum with the Curriculum of Citizenship Education Subject to Improve Students Islamic Personality - Mastuhi; Muhibbin Shah; Agus Salim Mansyur; Muhammad Erihadiana (Journal of Islamicate Studies, 2022)
Integrated curriculum is a curriculum which integrates a subject matter to another ones. Integrated curriculum at schools under the boarding school is clear to wish in order that their students have Islamic behavior, besides they have good knowledge. Integrated curriculum of the Islamic religious education on the curriculum of citizenship education subject is also to improve students’ Islamic behavior. The result’ of the research showed that:. The substances of integrated curriculum of the Islamic religious education on the curriculum of citizenship education subject to improve students’ Islamic behavior are honest, responsible, empathy, creative, discipline and consistent, hard worker, communicative, polite attitude, and sense of care attitude; The process of implementation of integrated curriculum of the Islamic religious education on the curriculum of citizenship education subject is to improve students’ Islamic behavior, the teacher motivates the students, explains the subject, directs, habituates, creates environment, and gives the tasks;